2011
DOI: 10.1002/ajpa.21594
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA perspectives on American colonization and population history

Abstract: Ancient DNA (aDNA) analyses have proven to be important tools in understanding human population dispersals, settlement patterns, interactions between prehistoric populations, and the development of regional population histories. Here, we review the published results of sixty-three human populations from throughout the Americas and compare the levels of diversity and geographic patterns of variation in the ancient samples with contemporary genetic variation in the Americas in order to investigate the evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 59 publications
3
56
0
6
Order By: Relevance
“…The coastal distribution of D4h3 was seen as consistent with coastal refugia models of migration during the LGM. It is worth noting that the results of these two aDNA studies provided evidence for the presence of three of the five major Native American haplogroups early in prehistory and are therefore consistent with the inference of Raff et al (2011) that mtDNA diversity was present and geographically structured early in the colonization process. Smith et al (2005) assayed mtDNA variation in all of the oldest human remains available for study (e.g., most samples over 7,500 years in age) and found that all of the major mtDNA haplogroups were present except for haplogroup X, confirming the range of mitochondrial diversity early in American populations.…”
Section: The Genetic Recordsupporting
confidence: 79%
See 3 more Smart Citations
“…The coastal distribution of D4h3 was seen as consistent with coastal refugia models of migration during the LGM. It is worth noting that the results of these two aDNA studies provided evidence for the presence of three of the five major Native American haplogroups early in prehistory and are therefore consistent with the inference of Raff et al (2011) that mtDNA diversity was present and geographically structured early in the colonization process. Smith et al (2005) assayed mtDNA variation in all of the oldest human remains available for study (e.g., most samples over 7,500 years in age) and found that all of the major mtDNA haplogroups were present except for haplogroup X, confirming the range of mitochondrial diversity early in American populations.…”
Section: The Genetic Recordsupporting
confidence: 79%
“…In this regard, the result of Fix's colonization simulation based on mtDNA data (2003) is not concordant with the simulations of colonization based on archeological data (Anderson and Gillam 2000;Surovell 2000). It is useful to recall that there is evidence that the striking geographic structure in mtDNA haplogroup frequencies in the Americas was established several thousand years before present (O'Rourke et al 2000;Raff et al 2011), shortening even more the temporal span over which such differentiation must have developed if it is constrained by the terminal LGM; presumably further weakening the argument for a single, late colonizing population as the primary source for later Native American populations (Volodko et al 2008).…”
Section: The Genetic Recordmentioning
confidence: 97%
See 2 more Smart Citations
“…A small number of aDNA results from the Americas would postpone the time of settlement by several thousands of years. The oldest samples studied (≥8 14 C ka BP), ostensibly the most informative for studies of the peopling of the continent, usually come from single individuals, while more recent ancient samples are suitable for the regional prehistory (Raff, et al 2011;Pickrell & Reich 2014;Llamas, et al 2016). Several findings of human remains from the Savannah of Bogotá (Figure 1a,1b) and from Boyacá (eastern Cordillera, Colombia) along with other relevant findings from elsewhere in the Americas (Pleistocene/ Holocene) are cited in Table 1.…”
Section: Introductionmentioning
confidence: 99%